PEMANFAATAN UDARA PANAS KONDENSOR MESIN PENDINGIN SEBAGAI SUMBER ENERGI PEMANAS AIR RUMAH TANGGA - Jeri Tangalajuk Siang; Aries Kamolan (Universitas Tridinanti Palembang, 2019)
The use of energy is important today due to the rapid decrease in fossil energy entire the world. The world should consider of using energy as efficient as possible. Waste energy from engines and other energy converters is released as hot air in the atmosphere. Waste heat energy is able to recover by using water heat exchanger. This research aims to experimentally examining the use of waste heat from room air conditioner as home energy source. A cross flow concentric pipe heat exchanger is used as the condenser for a room air conditioner to cover the exhaust energy from the condenser. The results shows that by using a concentric pipe condenser, the exhaust energy is benefit to decrease the paid energy equal to Rp. 57.000,- monthly electricity bill. The other supplementary beneficial equal to Rp. 564.249,- electricity bill gained from exhaust energy of the air conditioner. Keywords: : hot air, energy source